Quality Assessment in FDG-PET/CT Imaging of Head-and-Neck Cancer: One Home Run Is Better Than Two Doubles - Van den Wyngaert, Tim; De Schepper, Stijn; Carp, Laurens (Frontiers in Oncology, 2020)
[18F]fluorodeoxyglucose (FDG) positron emission tomography (PET) / computed tomography (CT) is indicated in head-and-neck cancer for the initial workup when clinically indicated (e.g. large tumors, clinically positive neck, cervical adenopathy from an unknown primary, etc), for the assessment of treatment response 12 weeks after completion of (chemo)radiotherapy, and during follow-up when there is suspicion of relapse. The successful implementation of FDG-PET/CT in routine clinical practice requires an in-depth understanding of the recent advances in physics and engineering that have significantly improved the imaging capabilities of PET/CT scanners (e.g. digital silicon photomultipliers, point-spread function modeling, and time-of-flight and Bayesian penalized likelihood reconstruction). Moreover, a coordinated harmonization effort from professional societies (e.g. EANM) and international bodies (e.g. IAEA) has resulted in the creation of quality assurance frameworks (e.g. QUANUM, EARL, GMP) and guidelines that collectively cover the entire spectrum from tracer production, hardware calibration, patient preparation and scan acquisition, to image interpretation (e.g. PERCIST, Hopkins criteria). The ultimate goal is to standardize the PET/CT technique and to guarantee accurate and reproducible imaging results for every patient. This review summarizes the recent technical breakthroughs in PET/CT scan design and describes the existing quality assessment frameworks with a focus on applications in head-and-neck cancer. Strict adherence to these harmonization efforts will enable leveraging the full potential of PET/CT and translate the proven benefits of this technique into tangible improvements in outcome for patients with head-and-neck cancer in routine clinical care.